CD4+ T Cells Play a Critical Role in Microbiota-Maintained Anti-HBV Immunity in a Mouse Model - Wu, Tingxin; Li, Fenglei; Chen, Yongyan; Wei, Haiming; Tian, Zhigang; Sun, Cheng; Sun, Rui (Frontiers in Immunology, 2019)
The ability of the host to clear hepatitis B virus (HBV) is closely correlated to the establishment of commensal microbiota. However, how microbiota affects anti-HBV immunity is still unclear. Using a well-known hydrodynamical HBV transfection mouse model and treatment with antibiotics (Atb), we explored the change in adaptive immunity (CD4+ cells, germinal center B cells and anti-HBs Ab). In our setting, normal mice exhibited complete clearance of HBV within 6 weeks post-hydrodynamic injection of HBV-containing plasmid, whereas Atb-treated mice lost this capacity, showing high serum level of hepatitis B surface antigen (HBsAg) without hepatitis B surface antibodies (anti-HBs), similar as what happened in Rag1−/− mice or CD4−/− mice, suggesting that microbiota may influence the function of CD4+ T cells. Furthermore, the numbers of splenic and hepatic effector CD4+ T cells (CD44hiCD62L−CD4+ T cells) both decreased with impaired function (IFN-γ synthesis), which resulted in lower frequency of germinal center B cells and CD4+ follicular helper T cells, and impaired anti-HBs production. We further tried to find the bacterial species responsible for maintaining anti-HBV immunity, and found that each antibiotic alone could not significantly influence HBV clearance compared to antibiotic combination, suggesting that global commensal microbial load is critical for promoting HBV clearance. We also confirmed that TLRs (e,g. TLR2, 4, 9) are not major players in immune clearance of HBV using their agonists and knock-out mice. These results suggest that commensal microbiota play an important role in maintaining CD4+ T cell immunity against HBV infection.